Streptococcus mutans-induced nephritis in rabbits. - Albini, B. (1985)
Intravenous administration of disrupted Streptococcus mutans into rabbits over 23-76 weeks led to severe nephritis involving glomeruli, tubules, and interstitium. Light-microscopic observation of glomeruli documented diffuse endocapillary proliferative glomerulonephritis accompanied often (65%) by epithelial crescents. Electron-microscopic observation revealed humps in glomeruli of 70% of kidney specimens. In the glomeruli of some rabbits, extensive fibrin deposits and sclerosis were evident. Immunofluorescence showed linear, granular, often ribbonlike or patchy immune deposits encompassing, in order of decreasing frequency, C3, IgG, streptococcal antigen, IgA, and IgM. The histopathologic and immunohistologic features of the nephritis seen in rabbits given S mutans thus shows many features of Streptococcus-associated nephritides in man, in particular, the diffuse glomerular nephritis encountered in subacute bacterial endocarditis. Further, analysis of nephritis induced by administration of S mutans may have implications for the evaluation and purification of dental caries vaccines.